Case Report: Mitral Valve Involvement and First-Degree Atrial-Ventricular Block in Two Patients With Multisystem Inflammatory Syndrome in Children - Di Filippo, Paola; Raso, Massimiliano; Cacciatore, Marta; Patacchiola, Roberta; Renda, Giulia; Rossi, Nadia; Chiarelli, Francesco (Frontiers in Pediatrics, 2021)
COVID-19 seems to be less frequent and severe in children compared to adults. Despite the very few symptoms usually found in children, great attention was recorded when in April 2020 a hyperinflammatory process in children with fever and multiorgan involvement after a paucisymptomatic COVID infection was reported. The United States Centers for Disease Control and the World Health Organization recognized and defined this syndrome as “Multisystem Inflammatory Syndrome in Children (MIS-C)”. We describe two cases of MIS-C presenting with fever, cutaneous rash and a mild cardiac involvement expressed with a transient mitral valve involvement and a first-degree atrioventricular block. Acute treatment was managed with intravenous immunoglobulin, oral aspirin and intravenous corticosteroids reaching consequent good outcome. Clinical characteristics, treatment management, follow-up and long-term evolution of children with MIS-C are still poorly defined. Further research is needed to better understand the pathogenesis of this newly described condition, to validate a high-level recommended therapy and a specific therapy tapering timings.